The relationship between family income and schooling attainment: Evidence from a liberal arts college with a full tuition subsidy program - Todd R. Stinebrickner; Ralph Stinebrickner (The University of Western Ontario, Department of Economics, 2000)
Researchers have long been interested in understanding why a Strong relationship between family income and educational attainment exists at virtually all levels of schooling. In part due to a recent increase in the disparity between the wages of college graduates and the wages of individuals with less than a college degree, there has been a specific interest in understanding why individuals from low income families are less likely to graduate from college than other students. Using unique new data obtained directly from a liberal arts school that maintains a full tuition subsidy program, this paper provides direct evidence that family environment reasons that are unrelated to the tuition costs of college are very important. The paper pays close attention to the issue of selection bias by deriving a set of seemingly very plausible conditions under which the estimator of interest is conservative. The findings, which suggest that non-trivial differences in educational attainment would exist even if tuition was zero for all students, have implications for expensive policy programs such as the full tuition subsidy program that was recently approved by the state of California.
Keywords: 330; Haushaltseinkommen; Bildungsverhalten; Statistischer Test; Kalifornien; USA